The Unfolding of Words : Commentary in the Age of Erasmus - Swan, Peter Michael, 1931-; Henderson, Judith Rice (Book collections on Project MUSE., 2012)
The Unfolding of Words brings together international scholarship to explore crucial changes in writers' interactions with religious and classical texts.